2018
DOI: 10.1177/0170840617747921
|View full text |Cite
|
Sign up to set email alerts
|

A Novel NGO Approach to Facilitate the Adoption of Sustainable Innovations in Low-Income Countries: Lessons from Small-scale Farms in Nicaragua

Abstract: There are about 500 million small-scale farms in low-income countries on the planet. Farmers have been slow to adopt a threefold set of sustainable agronomic practices known as “conservation agriculture” (CA) that have been shown to double productivity. Our study of a novel CA project in Nicaragua, organized based on principles that counter convention, may point to improved ways of understanding and managing sustainable innovations in low-income countries. In particular, by connecting core ideas from the innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 71 publications
0
25
0
1
Order By: Relevance
“…Extant studies suggest that a critical step in poverty interventions by NGOs is to be sensitive to the local norms, values, knowledge bases and relations (Dyck & Silvestre, 2018; McKague et al, 2015; Venkataraman et al, 2016). Our findings suggest that when such sensitivity is lacking, design failures become more likely – misalignments between intervention and initial contextual conditions that likely may affect the development path of the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant studies suggest that a critical step in poverty interventions by NGOs is to be sensitive to the local norms, values, knowledge bases and relations (Dyck & Silvestre, 2018; McKague et al, 2015; Venkataraman et al, 2016). Our findings suggest that when such sensitivity is lacking, design failures become more likely – misalignments between intervention and initial contextual conditions that likely may affect the development path of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown that successful interventions require NGOs to engage in contextual bridging, defined as 'a process involving the transfer of new meanings, practices, and structures into a given context in a way that is sensitive to the norms, practices, knowledge, and relationships that exist in that context ' (McKague et al, 2015' (McKague et al, , p. 1063. NGOs may hire local staff to bridge indigenous knowledge (McKague et al, 2015), make use of 'insiders' to win the trust of the targeted beneficiaries and build rapport with them (Venkataraman et al, 2016), draw on local norms, beliefs and power structures to promote novel ideas (Mair et al, 2016) or engage deeply with the local community (Dyck & Silvestre, 2018). Contextualizing interventions is necessary for the newly introduced social structures, standards and practices to be accepted by local stakeholders and become embedded in the existing institutional environment (Schouten, Vellema, & Van Wijk, 2016).…”
Section: Institutional Voids and Ngo Interventionsmentioning
confidence: 99%
“…Food often serves as a fascinating empirical context in which to investigate and address a range of issues and questions deemed relevant for the field of organization studies. Recent examples include research into categories (Delmestri & Greenwood, 2016), standards (Reinecke, Manning, & von Hagen, 2012), careers (Slavich & Castellucci, 2016), institutional maintenance (Croidieu, Soppe, & Powell, 2018; Gill & Burrow, 2018), corporate social responsibility (Souza-Monteiro & Hooker, 2017), online communities (Moser et al, 2013), creativity (Croidieu, Rüling, & Boutinot, 2016; Koch, Wenzel, Senf, & Maibier, 2018), professional work and identity (Clarke & Knights, 2018, 2019; Hamilton, 2013), knowledge sharing (Moser & Deichmann, 2020) and innovation (Feuls, 2018; Dyck & Silvestre, 2019; Slavich, Svejenova, Opazo, & Patriotta, 2020). Food may be studied as a bonding element in emerging cultural practices, for example, in the recent transformation of the prominent British social institution of the pub into gastropub (Lane, 2018).…”
Section: Food Organizing: a Conceptual Frameworkmentioning
confidence: 99%
“…Conservation agriculture seeks to develop practices and encourage crops that save resources in crop production thereby conserving the environment as well as enhancing profits of farmers Dyck and Silvestre (2019), Pittelkow et al (2015), Umar (2014) and Wall (2007) Value chain analysis Analyzing the whole value chain to see opportunities for value creation and reappropriation at different points in the supply chain Staritz (2012), Godfrey et al (2019), Thai (2017), McMichael (2013, Webber and Labaste (2010), Bresnyan (2008), and Taylor (Campos-Climent et al, 2012;Nyamah et al, 2017). Some authors have discussed the voluntary actions of groups to pursue common objectives in terms of "community-based organizations" (Kruijssen et al, 2009) and "collective actions" (Markelova et al, 2009).…”
Section: Organic Agriculture and Fairtrade Initiativesmentioning
confidence: 99%
“…There are more than 500m small farmers on the planet (Dyck and Silvestre, 2019). It is widely recognized that farmers all over the world, and in developing countries, in particular, do not get a fair share of their efforts and investments (Loconto and Simbua, 2012).…”
Section: Introductionmentioning
confidence: 99%